(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This review will provide the vital information about some pharmacological agents which are Neurotoxic. Through this update, Anti-cancer, Anti-bacterial, Analgesic, Psychoactive drug and Anabolic steroid medication are reported briefly regarding their neurotoxic mechanisms. In this review all information regarding neurotoxic drugs is collected from 2020 published work by Web of science, Scopus, PubMed and Google Scholar. It is concluded that all these drugs which the part of our study are neurotoxic. There is need to discover some method to reduce their toxicity and to avoid the chronic use of these medications.